A pervasive role for biomass burning in tropical high ozone/low water structures - Daniel C. Anderson (Nature Portfolio, 2016)
High ozone and low water structures in the tropical western Pacific are commonly attributed to transport from the stratosphere or mid-latitudes. Here, Anderson et al. show these structures actually result from ozone production in biomass burning plumes and large-scale descent of air within the tropics.